Studi Fenomenologi: Pengalaman Koping Pada Pasien Kanker Serviks - Hernandia Distinarista (Indonesian National Nurses Association (INNA) of Central Java, 2019)
A cancer diagnosis not only affects patients but also family and friends. It is not uncommon for patients to feel anxious, scared and stressed when they hear the word